Postmarket Safety Communication for Protection of Public Health: A Comparison of Regulatory Policy in Australia, Canada, the European Union, and the United States. Issue 6 (11th October 2020) - Bhasale, Alice L.; Sarpatwari, Ameet; De Bruin, Marie L.; Lexchin, Joel; Lopert, Ruth; Bahri, Priya; Mintzes, Barbara J.
Abstract : In the wake of the withdrawal of the nonsteroidal anti‐inflammatory drug rofecoxib, regulators worldwide reconsidered their approach to postmarket safety. Many have since adopted a "life cycle" approach to regulation of medicines, facilitating faster approval of new medicines while planning for potential postmarket safety issues. A crucial aspect of postmarket safety is the effective and timely communication of emerging risk information using postmarket safety advisories, commonly issued as letters to healthcare professionals, drug safety bulletins, media alerts, and website announcements. Yet regulators differ in their use of postmarket safety advisories. We examined the capacity of regulators in the United States, Europe, Canada, and Australia to warn about postmarket safety issues through safety advisories by assessing their governance, legislative authority, risk communication capabilities, and transparency.